Aroandes, una tecnologia para la cosecha manual de cafe con alta calidad - Lopez F, H.A.=700 1 Ramirez G, C.A.; Oliveros T, C.E.; Sanz U, J.R.
(Es, En)
Ilus., 4 ref.
Keywords: COFFEA ARABICA; COSECHA; METODOS MECANICOS; ERGONOMIA; COLOMBIA; CAFE CEREZA